A Spoonful of Sugar: Privatization and Popular Support for Reform in the Czech Republic - John S. Earle; Scott Gelbach (W.E. Upjohn Institute for Employment Research, 2002)
We analyze the role of privatization in creating a constituency for economic reform, markets, and democratic institutions, focusing on the Czech Republic. Drawing on a 1996 survey, we examine the 1459 respondents' opinions on reforms, economic policies and systems, the legitimacy of transition, and democratic values. Using ordered probit estimation, we find that receiving property through restitution is strongly associated with support for reform and markets. Concerning voucher privatization, we find positive effects for participants retaining shares, but little impact of participation alone. Our simulations suggest that policy designs have substantial consequences for citizens' support of reforms, markets, and democracy.
Additional information: A revised version of this paper appears in Economics and Politics, Vol. 15, No. 1 (March 2003). See http://ideas.repec.org/a/bla/ecopol/v15y2003i1p1-32.html. Please cite this revised version.
Keywords: D72; L33; P26; P35; 330; Czech; privatization; Earle; Gelbach